Using Online Comments to Explore General Attitudes Towards Learning Mandarin Chinese as a Foreign Language in the UK - Yu, Shanjiang (My University, 2023)
Due to the impact of global English, theoretical research on the motivation of L2 learning in the past few decades has been dominated by studies involving learning English. Questions need to be asked as to what degree those results apply to the situation relating to other languages, especially non-European languages. Different from conventional studies, this explorative study sets out to investigate people's attitudes towards Chinese as a foreign language (CFL) in the UK through public comments on a major media platform. Among the findings, the majority of comments are negative about CFL and the integrative/ intrinsic dimension is crucial. Language difficulty is not the main reason why people are not studying Chinese as it is widely believed. Among the specific factors, English being the global language is the biggest barrier. Based on this finding, it seems reasonable to argue that, for an emerging regional/ global language like Chinese, more attention should be given to integrative/ intrinsic motivation rather than instrumental benefit. Cultural and social-political factors are also discussed, and suggestions are made for more effective promotion of CFL as well as for other emerging languages.
Keywords: 4703 Language studies; 4704 Linguistics; 4705 Literary studies